Exogenous melatonin strongly affects dynamic photosynthesis and enhances water-water cycle in tobacco - Sun, Hu; Wang, Xiao-Qian; Zeng, Zhi-Lan; Yang, Ying-Jie; Huang, Wei (Frontiers in Plant Science, 2022)
Melatonin (MT), an important phytohormone synthesized naturally, was recently used to improve plant resistance against abiotic and biotic stresses. However, the effects of exogenous melatonin on photosynthetic performances have not yet been well clarified. We found that spraying of exogenous melatonin (100 μM) to leaves slightly affected the steady state values of CO2 assimilation rate (AN), stomatal conductance (gs) and mesophyll conductance (gm) under high light in tobacco leaves. However, this exogenous melatonin strongly delayed the induction kinetics of gs and gm, leading to the slower induction speed of AN. During photosynthetic induction, AN is mainly limited by biochemistry in the absence of exogenous melatonin, but by CO2 diffusion conductance in the presence of exogenous melatonin. Therefore, exogenous melatonin can aggravate photosynthetic carbon loss during photosynthetic induction and should be used with care for crop plants grown under natural fluctuating light. Within the first 10 min after transition from low to high light, photosynthetic electron transport rates (ETR) for AN and photorespiration were suppressed in the presence of exogenous melatonin. Meanwhile, an important alternative electron sink, namely water-water cycle, was enhanced to dissipate excess light energy. These results indicate that exogenous melatonin upregulates water-water cycle to facilitate photoprotection. Taking together, this study is the first to demonstrate that exogenous melatonin inhibits dynamic photosynthesis and improves photoprotection in higher plants.